Fabrication of Polyvinyl alcohol / Ginger / Oregano Nanocomposite Electrospun Nanofibers and their Enhanced Antibacterial and Antioxidant Activities - Essam, Mohga (AUC Knowledge Fountain, 2019)
The rate of bacterial resistance is increasing at an enormous rate making many antibiotics ineffective and resulting in oxidative stress. Furthermore, synthetic antibiotics have major side effects that can be life-threatening. Recently, scientific research started shifting its interest from targeting synthetic antibiotic products to natural-based products such as essential oils (EOs) that are eco-friendly, biocompatible, biodegradable, and effective when exposed to pathogens. Several reports about ginger essential oil (GEO) and oregano essential oil (ORGEO) have been recently reported that they possess immense antibacterial and antioxidant properties. The main objective of this research was to efficiently synthesize electrospun nanofibers (NFs) using from polyvinyl alcohol (PVA) and the surfactant tween-80 (T80) to form PVA/T80/GEO, PVA/T80/ORGEO, and PVA/T80/GEO/ORGEO. Furthermore, investigation of their potential antioxidant activities and their antibacterial activities against Escherichia coli (E.coli) and Staphylococcus aureus (S. aureus) was conducted. The fabrication of the nanofibers was accomplished by the electrospinning method by applying high voltages applied to the polymer which forces it to spin-off in the form of spray forming NFs that get collected on the collector plate. Then, characterization of the NFs was successfully performed by the Scanning Electron Microscopy (SEM), Fourier Transform Infrared (FT-IR) spectroscopy technique. Also, to study the antibacterial effect, E. coli and S. aureus were cultured in Lysogeny Broth liquid media for a day at a temperature of 37 Â°C. After that, the NFs from different nanocomposite were exposed to the two types of bacteria in a three-well plate. Optical density measurements were then taken on hourly basis using a spectrophotometer to analyse the antibacterial effect. In addition, antioxidant activity was tested by adding 2,2-diphenyl-1-picrylhydrazyl (DPPH) to the NFs for 2 hrs and monitoring them using ultraviolet visible spectroscopy (UV-Vis). The results obtained show enhanced antibacterial and antioxidant activities of the nanocomposite NFs obtained from combinations containing either PVA/T80/GEO, PVE/T80/ORGEO, and PVA/T80/GEO/ORGEO. In addition, although GEO and ORGEO have already been well-researched EOs and their antimicrobial and antioxidant properties are vastly known, the nanocomposite NFs proved to be much more efficient as antibacterials and antioxidants than pure EOs to be used efficiently in biomedical applications.